Biodistribution of unmodified cardiosphere‐derived cell extracellular vesicles using single RNA tracing. Issue 1 (10th January 2022) - Ciullo, Alessandra; Li, Chang; Li, Liang; Ungerleider, Korie C.; Peck, Kiel; Marbán, Eduardo; Ibrahim, Ahmed G.E.
Abstract: Extracellular vesicles (EVs) are potent signalling mediators. Although interest in EV translation is ever‐increasing, development efforts are hampered by the inability to reliably assess the uptake of EVs and their RNA cargo. Here, we establish a novel qPCR‐based method for the detection of unmodified EVs using an RNA Tracer (DUST). In this proof‐of‐concept study we use a human‐specific Y RNA‐derived small RNA (YsRNA) we dub "NT4" that is enriched in cardiosphere‐derived cell small EVs (CDC‐sEVs). The assay is robust, sensitive, and reproducible. Intravenously administered CDC‐sEVs accumulated primarily in the heart on a per mg basis. Cardiac injury enhanced EV uptake in the heart, liver, and brain. Inhibition of EV docking by heparin suppressed uptake variably, while inhibition of endocytosis attenuated uptake in all organs. In vitro, EVs were uptaken more efficiently by macrophages, endothelial cells, and cardiac fibroblasts compared to cardiomyocytes. These findings demonstrate the utility of DUST to assess uptake of EVs in vivo and in vitro.